Characteristics of wetlands used by migrant dabbling ducks in Oklahoma, USA - Heitmeyer, Mickey E; Vohs, Paul A, Jr (Wildfowl, 1984)
The geographical and habitat distribution, habitat selection factors, and activities of migrant dabbling ducks were studied in autumn 1979 and spring 1979 and 1980 on small scattered wetlands present in Oklahoma. Dabbling duck species were most abundant in provinces that contained the greatest number and quality of preferred habitats. Both seasonal and long-term wetland dynamics influenced habitat availability and habitat selection. American Wigeon Anas americana and Gadwall A. strepera both selected vegetated wetlands but were spatially separated; Blue-winged Teal A. discors and Shoveler A. clypeata occurred in similar provinces but used different habitats; and Green-winged Teal A.crecca, Wood Duck Aix sponsa and Mallard Anas platyrhynchos all selected natural floodplain wetlands but either occurred in different provinces or differed ecologically. While the exact number of waterfowl using small wetlands in Oklahoma as migration stopover areas is unknown, these wetlands, especially natural basins, appear to serve an important role in maintaining migrant dabbling duck populations in the central United States.